Development of Molecular Structure Props to Support Science Learning - Fatmawati Fatmawati (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
Science subjects are one of the lessons that students often consider difficult, this can be seen from the students' learning outcomes which are not yet optimal. Apart from that, sometimes misconceptions are found when studying material in the field of science learning. This research aims to develop molecular structure teaching aids to support science learning. The type of research used is Research and Development (RD) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data collection techniques are carried out through questionnaires, observation, and documentation. The results of the research were that the expert assessment was 85% with very appropriate criteria, and student response data was 95.6% with very interesting criteria. Apart from that, students stated that the teaching aids developed were very interesting, creative, easy to understand, and very good. Direct test results also show that there is an increase in students' understanding of using teaching aids. It can be concluded that the teaching aids developed are suitable and effective for use in the learning process in order to support students' learning in the field of science.